Juridical Study on the Negligence of Coal Mining Companies on Corporate Social Responsibility for the Community Affected by Mining Activities - Laurensia Mutiara Anindya; Meiriana Meiriana (Journal Of Social Science (JoSS), 2025)
Coal mining activities in Indonesia have a significant social and environmental impact on the communities around the mining area. In this context, Corporate Social Responsibility (CSR) is a legal and social instrument that must be carried out by the company as a form of responsibility to the affected communities. This study aims to juridically analyze the forms of negligence of mining companies in the implementation of CSR, as well as evaluate the effectiveness of regulations that regulate these obligations. With a normative juridical approach and case studies, this study identifies legal loopholes, weak supervision, and lack of community participation in the implementation of CSR. The results of the study show that CSR negligence by coal mining companies occurs in various forms, ranging from the absence of relevant CSR programs to manipulative and unsustainable implementation. The impact includes economic losses, environmental damage, social conflicts, and human rights violations. Legally, this negligence can be categorized as an unlawful act (PMH) and gives rise to civil and criminal liability. However, law enforcement is still weak due to the absence of standard CSR implementation standards and limited public access to legal mechanisms. This study recommends reform of CSR regulations through strengthening legal sanctions, establishing independent supervisory bodies, and implementing rights-based approaches in the implementation of CSR. With these steps, it is hoped that the negligence of mining companies can be minimized and the affected communities obtain fairer and more sustainable legal protection.